COMPARATIVE ANALYSIS OF GROSS PRODUCTION SHARING CONTRACTS (GPSC) AND CLASSICAL PRODUCTION SHARING CONTRACTS (PSC) (World Conference on Engineering and Technological Sciences, 2026)
This thesis analyzes the legal and economic aspects of Gross Production Sharing Contracts (GPSC) used in Iraq. Compared to classical Production Sharing Contracts (PSC), the GPSC model has several distinctive features: a rigid cost recovery cap, centralized state control, and often a fixed remuneration system. The practical aspects of the model are illustrated using the example of the Halfaya field. Furthermore, a comparative analysis of both models under identical conditions is presented, demonstrating that the GPSC model is primarily suitable for high-risk countries, while the classical PSC is preferable for stable countries (including Uzbekistan).
Keywords: Gross Production Sharing Contract, GPSC, PSC, Iraq, Halfaya, cost recovery cap, fixed fee, investment, risk.